Massive subsurface ice formed by refreezing of ice-shelf melt ponds - Hubbard, Bryn; Luckman, Adrian; Ashmore, David W.; Bevan, Suzanne; Kulessa, Bernd; Kuipers Munneke, Peter; Philippe, Morgane; Jansen, Daniela; Booth, Adam; Sevestre, Heidi; Tison, Jean-Louis; O’Leary, Martin; et al. (Nature communications, 2016)
Surface melt ponds form intermittently on several Antarctic ice shelves. Although implicated in ice-shelf break up, the consequences of such ponding for ice formation and ice-shelf structure have not been evaluated. Here we report the discovery of a massive subsurface ice layer, at least 16 km across, several kilometres long and tens of metres deep, located in an area of intense melting and intermittent ponding on Larsen C Ice Shelf, Antarctica. We combine borehole optical televiewer logging and radar measurements with remote sensing and firn modelling to investigate the layer, found to be ∼10 °C warmer and ∼170 kg m −3 denser than anticipated in the absence of ponding and hitherto used in models of ice-shelf fracture and flow. Surface ponding and ice layers such as the one we report are likely to form on a wider range of Antarctic ice shelves in response to climatic warming in forthcoming decades. The influence of surface ponding on the interior of ice shelves is currently unknown. Here, the authors combine surface and borehole geophysics on the Larsen C Ice Shelf, Antarctica, with remote sensing and modelling and show how pond refreezing increases ice shelf density and temperature.